A strategy to minimize the sensing voltage drift error in a transistor biosensor with a nanoscale sensing gate - Son, Hyun Woo; Jeun, Minhong; Choi, Jaewon; Lee, Kwan Hyi (DOVE MEDICAL PRESS LTD, 2017)
An ion-sensitive field-effect transistor ( ISFET) biosensor is thought to be the center of the next era of health diagnosis. However, questions are raised about its functions and reliability in liquid samples. Consequently, real-life clinical applications are few in number. In this study, we report a strategy to minimize the sensing signal drift error during bioanalyte detection in an ISFET biosensor. A nanoscale SnO2 thin film is used as a gate oxide layer (GOL), and the surface of the GOL is chemically modified for improving bioanalyte-specific binding and for reducing undesirable ion reactions in sample solutions. The ISFET biosensor with surface-modified GOL shows significantly reduced sensing signal error compared with an ISFET with bare GOL in both diluted and undiluted phosphate buffered saline solutions.
Keywords: FIELD-EFFECT TRANSISTOR